Multi Agent Model Analysis in Identifying the Relationship Between Productivity Level, Production Cost and Product Selling Price - Kushariyadi, Kushariyadi; Sihombing, Dina Agnesia; Husaini, Husaini; Turyadi, Ito; Zakaria, Muhammad (Malikussaleh University, Aceh, Indonesia, 2024)
This study aims to analyze the remuneration strategy and the dynamics of a highly competitive market that affect employee productivity and satisfaction. This research method uses a quantitative approach combined with comparative statistics. Companies often choose a per-piece pay strategy to encourage efficiency and productivity while managing labor costs. However, companies may shift to a profit-sharing system to increase employee engagement and loyalty. Differentiation of payment schemes, such as performance-based incentives, plays an important role in attracting and retaining talent and aligning strategies with business goals, which in turn helps manage labor costs and reduce competitive pressures. Productivity and price sensitivity of demand also influence company strategy in markets with high productivity and low demand sensitivity, companies tend to adopt more innovative strategies, while in markets with low productivity and high costs, they often implement more homogeneous and conservative strategies. Further studies are necessary to explore additional factors such as differences in recruitment strategies, industry characteristics, and other variables that influence company decisions in remuneration strategies and labor distribution. Understanding these findings enables companies to design more effective remuneration strategies based on market conditions and their workforce requirements.